1987
DOI: 10.1093/fampra/4.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Correlates of Fatigue in a University Family Health Centre

Abstract: To delineate the demographic correlates of the fatigued patient, 297 patients attending a family practice centre were investigated. Women were more frequently tired than were men; patients with less than a college education were over-represented, and employed persons were more robust than the unemployed. Fatigue was also associated with lack of exercise, nightly wakening and the presence of children less than six years old in the household. There were no significant relationships between fatigue and age, smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
1
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 0 publications
2
13
1
1
Order By: Relevance
“…9 Age and marital status had no effect on fatigue, and this is in agreement with other studies. 2 The prevalence of anxiety was 25.8% in males and 47.1% in females, and this is higher than found previously. El-Rufaie found the prevalence of minor psychiatric morbidity to be 27.6%.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…9 Age and marital status had no effect on fatigue, and this is in agreement with other studies. 2 The prevalence of anxiety was 25.8% in males and 47.1% in females, and this is higher than found previously. El-Rufaie found the prevalence of minor psychiatric morbidity to be 27.6%.…”
Section: Discussioncontrasting
confidence: 52%
“…Fatigue was increased in those females who were illiterate or had no education, and this has been noted in other studies. 2,9 Over half the male subjects and a third of female subjects exercised regularly. Exercise was associated with less physical fatigue in males, and increasing BMI was mildly associated with fatigue in females, confirming previous study findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors found no correlations (Sugarman and Berg, 1984;Chen, 1986;Valdini et al, 1988;Ridsdale et al, 1993). Others have found inverse correlations (Tibblin et al, 1990) or positive but weak correlations if the duration of the fatigue was taken into account (David et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In a study involving randomly selected patients of a health care centre. 45% were scored as fatigued (Valdini et al 1987). More recently.…”
mentioning
confidence: 99%